Assessing the long-term interactions of climate change and timber markets on forest land and carbon storage. (13th January 2021) - Favero, Alice; Mendelsohn, Robert; Sohngen, Brent; Stocker, Benjamin
Abstract: This study provides a comprehensive assessment of the environmental and economic impacts of climate change on global and regional forests from now through 2200. By integrating the representative concentration pathway (RCP) 2.6 and RCP 8.5 emission scenarios with climate models, a vegetation model, socio-economic scenarios, and a forest economic model, the study explores long run adjustments of both ecosystems and markets to climate change that have not been studied before. The ecological model suggests that global forest productivity increases under RCP 8.5. The overall supply of timber expands faster than demand through the 23rd century lowering timber prices and creating net benefits in the timber sector. Consumers benefit the most from the lower prices but these same low prices tend to damage forest owners, especially in the tropics. Even without a formal sequestration policy, average global forest carbon is projected to increase by 6%–8% by 2100. Under the RCP 2.6, forest carbon remains stable through 2200 but under RCP 8.5 it is simulated to increase by another 8% with a very heterogeneous distribution across world regions. Under both RCPs, global forest area is projected to increase relative to a no-climate change case until 2150, but possibly decline thereafter.